PENGARUH LUAS LAHAN PERSAWAHAN, MODAL DAN TENAGA KERJA TERHADAP PENDAPATAN PETANI SAWAH PADA KECAMATAN SYAMTALIRA ARON KABUPATEN ACEH UTARA (Studi Kasus Kemukiman Teupin Punti) - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2018)
The purpose of this study is to see the effect of paddy field area, capital and labor force on the income of rice farmers in the District of Syamtalira Aron, North Aceh Regency. The data used in this study is the primary data in Ketupin Teupin Punti. Methods of data analysis is to use multiple linear regression analysis. The result of land acquisition did not significantly and positively affect the income of wetland farmers, capital and labor significantly and positively affect the income of rice farmers in Kecamatan Syamtalira Aron Kabupaten Aceh Utara.